2013
DOI: 10.1073/pnas.1316449110
|View full text |Cite
|
Sign up to set email alerts
|

Development of socio-emotional competence in bonobos

Abstract: Social and emotional skills are tightly interlinked in human development, and both are negatively impacted by disrupted social development. The same interplay between social and emotional skills, including expressions of empathy, has received scant attention in other primates however, despite the growing interest in caring, friendships, and the fitness benefits of social skills. Here we examine the development of socio-emotional competence in juvenile bonobos (Pan paniscus) at a sanctuary in the Democratic Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 48 publications
3
83
0
2
Order By: Relevance
“…The predominant reason for not helping appears to be an excessive amount of personal anxiety. Bonobo apes who show more anxiety, measured by how much they scratch themselves, and who take longer to recover from a stressful event show less consolation behavior toward other bonobos in distress (Clay & de Waal, 2013 ). This fi nding dovetails beautifully with human literature suggesting that to use empathy for helping or caring, an individual must overcome personal distress, a process typically termed self-or down-regulation.…”
Section: What Prevents Helping?supporting
confidence: 57%
“…The predominant reason for not helping appears to be an excessive amount of personal anxiety. Bonobo apes who show more anxiety, measured by how much they scratch themselves, and who take longer to recover from a stressful event show less consolation behavior toward other bonobos in distress (Clay & de Waal, 2013 ). This fi nding dovetails beautifully with human literature suggesting that to use empathy for helping or caring, an individual must overcome personal distress, a process typically termed self-or down-regulation.…”
Section: What Prevents Helping?supporting
confidence: 57%
“…Similarly, the bonobos' rearing history may also explain differences in tolerance between studies. Although Wobber and Hare [2011] did not find differences in cognitive performance between orphaned and mother-reared apes, Clay and de Waal [2013] suggested that mother-reared bonobos show better emotional regulation and social competence. It is possible that these behavioural differences extend towards food-related strategies, including mechanisms to avoid food competition.…”
Section: Discussionmentioning
confidence: 81%
“…Note, however, that female primates are much more likely to suffer from a lack of maternal support than to benefit from it, not only in terms of rank outcomes (Fig. 2), but also in terms of behavioural and social development (Botero et al, 2013; Clay & de Waal, 2013; Missakian et al, 1972), as well as mortality risk (Hasegawa & Hiraiwa, 1980). …”
Section: Discussionmentioning
confidence: 99%